Haemolysis during diabetic ketoacidosis treatment in two girls withincomplete glucose-6-phosphate dehydrogenase deficiency - Errico, M. K.; Iovane, B.; Bernardini, A.; Gliati, et al., D. (Acta Biomedica Atenei Parmensis, 2009)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a typical X-linked enzymopathy causing severe haemolytic anaemia in males, and mild to moderate anaemia in homozygous females. Haemolysis due to G6PD deficiency in patients with type 1 diabetes mellitus (T1DM) has been principally reported in males, but is uncommon. During the last 10 years 2 girls with an unknown incomplete G-6-PD deficiency showed haemolysis during the treatment of DKA at the onset of T1DM. We speculate that the patients here described showed haemolytic anaemia as a phenotypic expression of the lyonization process and/or an uncommon penetrance of the defective gene. Haemolysis occurred when blood glucose levels were returning to normal values. In normal red blood cells, G6PD provides a source of reducing power for maintaining sulphydryl groups (SH) and facilitating the detoxification of free radicals and peroxides. During insulin i.v. infusion the copious glucose available due to the hyperglycaemia progressively decreased and affected the old red blood cells to generate nicotinamide adenine dinucleotide (NADPH), a crucial source for energy-dependent functions. This NADPH loss could have enhanced the rate of all factors such as methaemoglobin generation, Heinz body formation, and lipid peroxidation, which occur in G6PD deficient cells in response to both endogenous and exogenous oxidants. The direct consequence of this phenomenon is an increased erytrocyte oxidant sensitivity and a loss of sulphydryl group availability causing premature red blood cell destruction.